THE ROLE OF SPORTS GAMES IN THE EDUCATIONAL AND TRAINING PROCESS OF STUDENTS (Conferencea, 2023)
The importance of motor activity and sports games in the life of students is revealed. Their role in the educational and training process is considered. The specifics of the development of physical qualities in various sports games are presented. The influence of game sports on the improvement of professional activity is reflected. The necessity and need of students in sports activity is determined.